Linking positive psychology to offender supervision outcomes: the mediating role of psychological flexibility, general self-efficacy, optimism, and hope - Woldgabreal, Yilma (Criminal justice and behavior, 2016)
This study examines the relationships between indicators of offender supervision outcomes and dimensions of positive psychological states (PPS). Results of a confirmatory factor analysis (CFA) revealed that the first-order positive psychology constructs converge to form a higher order construct of PPS which was inversely associated with supervision outcomes. Furthermore, the mediating effect of PPS on the relationship between criminogenic risk factors and all offender supervision outcome variables was statistically significant, suggesting that offenders with heightened PPS are likely to have fewer criminogenic risk factors and are less likely to be reported for technical violation, charged, reconvicted, and imprisoned. The implications of these findings for correctional theory, practice, and policy conclude the article.